Advertising Ideology: Using Crowd-Sourced Measurement to Understand Campaigns. Issue 2 (3rd April 2021) - Clarke, Andrew J.; Gray, Thomas R.; Hughes, Adam G.
Abstract : We develop a subjective measure of candidate ideology in political communication, based on human coders evaluations of ideological position-taking in campaign advertisements. Our dynamic measure allows researchers to track campaign strategies within an election cycle and across ideologically distinct groups of voters. As an application of our approach, we analyze candidates ideological brand building in US House and Senate elections in 2010 and find evidence that structural features of US elections constrain the ideological brands of congressional candidates. We show that Democratic Senate candidates represented themselves as ideologically liberal in areas that strongly supported President Obama in 2008, but moderated their ideological message in more competitive areas. By contrast, we find no evidence of strategic branding among Republicans. Our results reveal one way in which fine-grained observational measures of political communications illustrate strategic ideological posturing that existing measures based on campaign donations or roll call votes cannot identify.